A dematel-topsis-wings approach to the classification of multimarket investment funds - Sallum, Frederico Silva Valentim (2018)
This paper analyzes the performance of 20 multimarket investment funds in the Brazilian market from May/2015 to April/2017 in order to categorize them into 4 performance levels. The cumulative rate and the funds' volatility are calculated in 2 periods among the total periods studied, in order to generate a mutual degree of influence among the funds of each group. Next, the WINGS method is applied. This method splits each group into 2 subgroups, generating the 4 levels of classification. The use of the methodology classified 5 funds in each subgroup. The data analysis compared the obtained classification with the classification established by the cumulative rate of the funds throughout the entire period and presented 4 ways to prioritize the decision for the funds ranked higher. These 4 ways of prioritizing the decision aim at assisting investors with different points of view.